Restriction on stating preferences in college admissions in Turkey - Kadir Doğan; Tolga Yuret (TÜSİAD-Koç University Economic Research Forum, 2008)
A central authority designs and implements the college admissions process in Turkey. All applicants are required to take an SAT-like test and submit their preferences over the departments. Then, the central authority places the applicants in departments by considering the test scores and stated preferences of the applicants and the capacities of the departments. This procedure generates a fair placement if there are no restrictions on stating preferences. However, the applicants are restricted to state preferences over at most 24 departments out of 4022 available departments. In this paper, by using the college admissions data set of the year 2005, we estimate that the number of applicants who had an unfair placement due to this restriction is equivalent to 2.4 percent of the number of applicants who placed in a department.
Keywords: I23; I28; C78; 330; Hochschulpolitik; Studium; Gerechtigkeit; Türkei